2009
DOI: 10.1186/1297-9686-41-32
|View full text |Cite
|
Sign up to set email alerts
|

Eleven generations of selection for the duration of fertility in the intergeneric crossbreeding of ducks

Abstract: A 12-generation selection experiment involving a selected line (S) and a control line (C) has been conducted since 1992 with the aim of increasing the number of fertile eggs laid by the Brown Tsaiya duck after a single artificial insemination (AI) with pooled Muscovy semen. On average, 28.9% of the females and 17.05% of the males were selected. The selection responses and the predicted responses showed similar trends. The average predicted genetic responses per generation in genetic standard deviation units we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Given that most studies have suggested that genetics has moderate effects on FSS, we estimated the h 2 of FE and FDD. The h 2 for the two traits were moderate, and higher genetic correlations of these traits between the two experimental periods were obtained, and these results were comparable to those obtained in previous reports [10,54,56]. The results indicated that the criteria we used to assess the characteristics of FSS were applicable and suitable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Given that most studies have suggested that genetics has moderate effects on FSS, we estimated the h 2 of FE and FDD. The h 2 for the two traits were moderate, and higher genetic correlations of these traits between the two experimental periods were obtained, and these results were comparable to those obtained in previous reports [10,54,56]. The results indicated that the criteria we used to assess the characteristics of FSS were applicable and suitable.…”
Section: Discussionsupporting
confidence: 87%
“…The usual criteria for evaluating that a species stores sperm range from simply finding sperm within a female RT to more thorough determinations of both the female physiology and the sperm viability [3]. Assessing the capacity of FSS by a series of fertile eggs has been broadly applied in avians [10,11,[53][54][55]. This idea will also be valuable to other oviparous animals, such as mosquitoes [46].…”
Section: Discussionmentioning
confidence: 99%
“…During the laying period, the ducks were fed a diet with 20% CP and 2810 kcal/kg ME. Drinking water and feed were provided ad libitum throughout the experimental period [26]. After 9 generations of selection, the SL had nearly twice the fertility performances of the CL.…”
Section: Animals and Dna Preparationmentioning
confidence: 99%
“…Mule duck meat production is developing in Europe, Vietnam and South East China ( Cheng et al, 2009 ). The mule ducks are sterile intergeneric hybrids which are produced by crossing Pekin or Kaiya (crossbred Pekin×White Tsaiya) female ducks with Muscovy drakes ( Cairina moschata ).…”
Section: Introductionmentioning
confidence: 99%